9. STRATEGIES, CHALLENGES, AND IMPLEMENTATION OF GENDER EQUALITY IN THE POLICE - Erika Merdiana Armono; Syamsunasir; Kerta Widana; Waspada Tedja Bhirawa; Suroso; Dwikatama (Jurnal TNI Angkatan Udara, 2026)
This study aims to analyze the implementation of gender mainstreaming policieswithin the Indonesian National Police (Polri) and identify challenges and gaps in theirimplementation. This study uses a qualitative approach with descriptive analysis methods toevaluate how the Indonesian National Police (Polri) has integrated gender equality principlesinto its operations and human resource policies, including policy documents, internal reports,and interviews with Polri personnel. The results indicate that although the Polri hasdemonstrated its commitment to gender mainstreaming through the issuance of Police ChiefRegulation Number 1 of 2022, its implementation remains suboptimal. Significant disparitiesexist between male and female police officers in recruitment, promotion, and job placement.Female police officers (Polwan) often face certain limitations not experienced by male policeofficers (Polki), such as specific recruitment criteria and a lack of opportunities for openpromotions. Consequently, the majority of female police officers remain confined toadministrative and health roles, with few reaching senior leadership positions.